การออกแบบและพัฒนาระบบสารสนเทศเพื่อสนับสนุนระบบการจ่ายไฟฟ้า สำหรับการไฟฟ้าส่วนภูมิภาค - ขัตติยา ยิ้มแย้ม (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this thesis is to design and develop an information system for supporting the distribution system of the Provincial Electricity Authority (PEA) as a centralized relational database. The data is fed into the system at substations, electric offices 1-2 , electric administration areas and stored in a database server at the central office. The web-base application software is installed only on a central application server. Users can connect to database via PEA Intranet network using web browser on their clients. The design of application software covers four parts. The first part is the distribution environment of each substation, its data contain the detail of substation environment. The second part is the load data entry system, its data is about the load used per period. The third part is related to information of electrical trip, its data is a electric trip history of anytime and is fed into the system at substations or electric offices 1-2. Its data will be used for reliability analysis. The fourth part is the statistic of trip locked out and trip reclosed of protection equipment, its data will be used for equipment maintenance planning. The information system developed in this research will be used for supporting the distribution system of the PEA and its database. It is useful for analysis and planning about the distribution environment, the electrical trip improvement and equipment maintenance.